Accelerating Kohn‐Sham response theory using density fitting and the auxiliary‐density‐matrix method. Issue 16 (9th May 2018) - Kumar, Chandan; Fliegl, Heike; Jensen, Frank; Teale, Andrew M.; Reine, Simen; Kjærgaard, Thomas
Abstract: An extension of the formulation of the atomic‐orbital‐based response theory of Larsen et al., JCP 113, 8909 (2000) is presented. This new framework has been implemented in LSDalton and allows for the use of Kohn‐Sham density‐functional theory with approximate treatment of the Coulomb and Exchange contributions to the response equations via the popular resolution‐of‐the‐identity approximation as well as the auxiliary‐density matrix method (ADMM). We present benchmark calculations of ground‐state energies as well as the linear and quadratic response properties: vertical excitation energies, polarizabilities, and hyperpolarizabilities. The quality of these approximations in a range of basis sets is assessed against reference calculations in a large aug‐pcseg‐4 basis. Our results confirm that density fitting of the Coulomb contribution can be used without hesitation for all the studied properties. The ADMM treatment of exchange is shown to yield high accuracy for ground‐state and excitation energies, whereas for polarizabilities and hyperpolarizabilities the performance gain comes at a cost of accuracy. Excitation energies of a tetrameric model consisting of units of the P700 special pigment of photosystem I have been studied to demonstrate the applicability of the code for a large system. Abstract : New framework is presented for the calculation of molecular response properties including: molecular excitation energies, polarizabilities and hyperpolarizabilities. The framework exploits techniques to significantly accelerate the evaluation of the Coulomb and exchange contributions to the response calculations and its efficiency is demonstrated by application to a tetrameric model of the units of the P700 special pigment of photosystem I.